Distribution and ecology of Rafflesia in Royal belum state park, Perak, Malaysia - Khaliz Kedri, Farah; Hamzah, Zulhazman; Sayzwani Sukri, Nur; Hajar Yaacob, Siti; Kyariatul Syafinie Abd Majid, Nur; Mokhtar, Nasihah; Fatimah Amir, Siti (International Journal of Engineering and Technology, 2018)
Rafflesia, the biggest flowers in the world are considered as majestic and are made as ecotourism icons for several places in the South East Asia. Currently, a total of 34 species of Rafflesia were recorded in this region. 7 species of Rafflesia are found in Peninsular Malaysia alone. This study was executed in Royal Belum State Park in the state of Perak. An updated on distribution of Rafflesia and its ecology are provided. The Rafflesia population was mapped using Global Positioning System [GPS]. While the size of Rafflesia host-plant was measured with the measuring tape and the amount of rainfall was obtained from the Meteorological Department of Malaysia. During this study, there were 2 species of Rafflesia encountered in Royal Belum State Park, namely Rafflesia cantleyi Solms-Laubach and Rafflesia kerri Meijer. The species were recorded at X-Ray trail, Sg. Gadong, and Sg. Kooi. A total of 8 populations were set up from these locations. It was found that the population and the distribution decreased in accordance with the habitat interruption by human intervention and natural factors such as wildlife trampling on the immature buds. Besides, it was found that the number of Rafflesia buds increases with the class size for host-plant of Rafflesia with coefficients of determination of R2=0.9866. However, various physiological and environmental factors were taken into consideration in efforts of conserving this unique flower. This study is important in order to preserve the population of Rafflesia at Royal Belum State Park.Â Â